Trends Of Utilization of Family Planning Methods at District Hospital Of Madhya Pradesh: A Retrospective Study - Garima Namdev; Swarna K Likhar; Mahesh Kumar Mishra; Arvind V Athavale; Umashanker Shukla (Medsci Publications, 2013)
Introduction: Population stabilization is the answer to curtail existing population growth of 1.2% in India and it can be achieved by effective use of contraception by couples. This study was designed to analyze the trends of utilization of different family planning methods in relation with socio-demographic factors at district hospital in last five years. Material and Method: A retrospective study was done by analyzing last five year records from family planning clinic at district hospital. Results: At family planning clinic, 1,84,522 individuals visited out of 12,33,753 individuals came for utilization of outdoor services at hospital during the five year period. Among them, 96% individuals utilized temporary methods and only 4% utilized permanent methods. Among temporary methods, 81.4% utilized condom, 10% OCP's and 3.8% IUCD, whereas among permanent methods, 3.4% utilized tubectomy and 0.6% vasectomy. The trend of utilization of family planning methods was found decreasing from 84.4% to 78% among male whereas increasing among female from 15.6% to 22% in last five year duration. Conclusion: The utilization of contraceptive methods was more common among male especially temporary (condom) as compared to the female but the utilization of permanent methods was more in rural folks as compared their urban counterparts.